OLEKSANDR OLES’ LYRICAL-INTIMATE DRAMATIC ART IN THE SCENE INTERPRETATION OF «YOUTH THEATRE» OF LES’ KURBAS: TYPOLOGY OF LITERARY AND ARTISTIC SYMBOLISM - Khorob, S. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The investigation has the attempt to typologize literary and artistic symbolism (its selfsublicience as national-cultural phenomenon) in the first decades of the XX-th centuru. Lerical-intimate dramatic art of Oleksandr Oles’ and its scene interpretation called «Dramatic essays of Oleksandr Oles’ in «Yoth Theatre» by Les’ Kurbas are taken for analysis. It is proved that symbolic-artistic thinking is characteristic for Ukrainian authors of the first decades of the XIX century. It exists not only in organic literary-scenic environment of that time, moreover it appears as original ideological-aesthetical and national-cultural phenome.